Systemic inflammation prevalence in patients with atherosclerotic cardiovascular disease and chronic kidney disease: a population-based study using a nationwide primary care database in Spain - Pesce, Giancarlo; Gusto, Gaelle; Johansen, Pierre; Khachatryan, Artak; Lopez-Ledesma, Bernabe; Vukmirica, Jelena; Cases, Aleix (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSystemic inflammation is recognised as a critical driver of atherosclerotic cardiovascular disease (ASCVD), especially in patients with comorbid chronic kidney disease (CKD). This study aims to assess the prevalence of systemic inflammation in the ASCVD population in Spain.MethodsOutpatient electronic medical records from The Health Improvement Network (THIN®) database were used to identify patients with ASCVD and a C-reactive protein (CRP) measurement ≥1 between January 2014 and July 2023 in Spain. The proportion of patients with systemic inflammation (defined as CRP ≥ 2 mg/L) was estimated at the first CRP measurement (index date) and at the end of the study. The patients' characteristics, comorbidities, and drug dispensation in the prior 12 months were reported by systemic inflammation status at the index date.ResultsOverall, 15,798 patients with ASCVD were included in the study (mean age: 71.1 years; 57% men), of whom 34% had CKD. The proportion of patients with systemic inflammation at the index date was 58% (65% among CKD patients) and 56% (62% among CKD patients) at the end of the study. Patients with systemic inflammation were more frequently smokers, obese, with comorbidities, and had higher low-density lipoprotein cholesterol and triglycerides levels than patients without systemic inflammation. Overall, patients with ASCVD and systemic inflammation used statins and aspirin less frequently compared to patients without systemic inflammation, while they used antibiotics, anticoagulants, and antihypertensives more frequently.ConclusionSystemic inflammation prevalence is high among patients with ASCVD in Spain, especially among patients with comorbid CKD. Therapeutic strategies focused on targeting systemic inflammation may have beneficial effects in reducing the burden of ASCVD.